Urban disaster mitigation : the role of engineering and technology - Cheng, Franklin Y.; Sheu, Maw Shyong (Elsevier, 1995)
Great loss of human life, structural damage, and social and economic upheaval occur repeatedly due to such natural hazards as earthquakes, typhoons, hurricanes, landslides, floods and tsunamis. Both the US and Taiwan, along with many other countries, have a history of such occurrences and a common need to reduce their effects. This volume includes papers from the fourth symposium workshop, held jointly between the US and Taiwan to discuss research and its application to multiple hazard mitigation. The workshop, <Q>Urban Disaster Mitigation, The Role of Engineering and Technology</Q>, discussed lessons learned from recent natural disasters; assessed results of Taiwan's multiple hazards research program and potential application to the US; and proposed further studies on subjects of mutual concern. Topics include recent scientific findings obtained in various natural hazard areas and assessment of actual and potential damage from earthquakes, floods and landslides. Of particular importance are measures that can be taken to mitigate these hazards ranging from use of new algorithms for structural engineering to warning systems for a given region. At a time when natural disasters are widespread, engineers play a key role. Construction methods and building codes are changing; current knowledge shapes the direction of these changes. The research results presented in these proceedings will benefit both the academic and practicing communities around the world, strengthening the relationship between these two important parties.